Characteristics of Febrile Children Admitted to the ICU Following an Unscheduled ED Revisit Within 72 h, a Case–Control Study - Chiang, Charng-Yen; Chen, Yu-Lun; Lin, Yan-Ren; Cheng, Fu-Jen; Wu, Kuan-Han; Chiu, I-Min (Frontiers in Pediatrics, 2020)
Objective: The purpose of this article was to demonstrate related characteristics of intensive care unit (ICU) admission after an unscheduled revisit by febrile children visiting the emergency department (ED). Method: We performed a retrospective study in a tertiary medical center from 2010 to 2016. Patients whose chief complaint was fever and who were admitted to the ICU following a 72-h return visit to the ED were included, and we selected patients who were discharged from the same emergency department for comparison. Results: During the study period, 54 (0.03%) patients met the inclusion criteria, and 216 patients were selected for the matched control group. Regarding clinical variables on initial ED visit, visiting during the night shift (66.7 vs. 46.8%, p = 0.010), shorter length of 1st ED stay (2.5 ± 2.63 vs. 3.5 ± 3.44 h, p = 0.017), and higher shock index (SI) (1.6 ± 0.07 vs. 1.4 ± 0.02, p = 0.008) were associated with ICU admission following a return visit. On the return ED visit, we found that clinical variables such as elevated heart rate, SI, white blood cell count, and C-reactive protein level were all associated with ICU admission. Furthermore, elevated SI and pediatric age-adjusted (SIPA) values were observed in the study group in both the initial (42.2 vs. 20.1%, OR:2.3 (1.37–4.31), p = 0.002) and return ED visits (29.7 vs. 6.9%, OR: 4.6 (2.42–8.26), p < 0.001). Conclusion: For children who visited the emergency department with a febrile complaint, elevated SIPA values on the initial ED visit were associated with ICU admission following an unscheduled ED revisit within 72 h.